Cointegration of Equity and Gold Markets: Evidence from Turkey - Küçükçolak, Ali; Büyükakın, Figen; Ilter Kucukcolak, Necla (International Journal of Economics and Financial Issues, 2019)
Gold has been an investment vehicle over the ages and helped investors to mitigate risks arise due to market fluctuations. In order to improve financial inclusion level and increase added value of the idle gold held by investors, there have been various instruments developed in recent decades. Likewise, derivative investments, mutual funds based on gold, gold certificates, gold based sukuks and bonds are various instruments issued in Turkey in order to mobilize gold within the financial system. In this paper, we are analyzing role of the gold within financial markets for the 2009-2017 period. In order to examine long term relationship, we utilize the co-integration methodology. Based on the analysis outcomes, Turkish stock and gold markets have a long run relationship and for portfolio diversification purposes, investors may benefit from this via adding gold to their stock market portfolio. Due to its low and negative correlation, increasing the inclusion of gold into financial system will enrich investment alternatives and diminish volatilities of the portfolios. Keywords: Gold, Portfolio Diversification, Cointegration JEL Classifications: G10, G11, O16 DOI: https://doi.org/10.32479/ijefi.7339